Familiness in Family Business: A Narrative Literature Review and Future Research Directions - Nadiah Mahmad Nasir; Khairul Akmaliah Adham (Journal of International Business, Economics and Entrepreneurship, 2023)
Family businesses, the backbone of the global economy, thrive on family elements (familiness). However, there is a lack of understanding of the concept of familiness, on which this study aimed to conduct a literature review. This narrative review study employed a scoping searching technique to identify and select articles related to familiness. In total, 36 articles were included for review and analysis. The study generated three emergent themes: i) definitions of familiness; ii) roles of familiness; and iii) factors that promote familiness. This narrative literature review extends the body of knowledge related to family businesses, particularly by outlining how familiness plays a predominantly positive role in influencing organisational outcomes. Furthermore, familiness may be the antecedent, mediator, and moderator of organisational outcomes, which potentially paves the way for establishing familiness as a potential source from which to generate resources for family businesses. The study also identified research gaps and provides some directions for future research.